Research on the Translation and Implementation of Stepping On in Three Wisconsin Communities - Schlotthauer, Amy E.; Mahoney, Jane E.; Christiansen, Ann L.; Gobel, Vicki L.; Layde, Peter; Lecey, Valeree; Mack, Karin A.; Shea, Terry; Clemson, Lindy (Frontiers in Public Health, 2017)
Objective Falls are a leading cause of injury death. Stepping On is a fall prevention program developed in Australia and shown to reduce falls by up to 31%. The original program was implemented in a community setting, by an occupational therapist, and included a home visit. The purpose of this study was to examine aspects of the translation and implementation of Stepping On in three community settings in Wisconsin. Methods The investigative team identified four research questions to understand the spread and use of the program, as well as to determine whether critical components of the program could be modified to maximize use in community practice. The team evaluated program uptake, participant reach, program feasibility, program acceptability, and program fidelity by varying the implementation setting and components of Stepping On. Implementation setting included type of host organization, rural versus urban location, health versus non-health background of leaders, and whether a phone call could replace the home visit. A mixed methodology of surveys and interviews completed by site managers, leaders, guest experts, participants, and content expert observations for program fidelity during classes was used. Results The study identified implementation challenges that varied by setting, including securing a physical therapist for the class and needing more time to recruit participants. There were no implementation differences between rural and urban locations. Potential differences emerged in program fidelity between health and non-health professional leaders, although fidelity was high overall with both. Home visits identified more home hazards than did phone calls and were perceived as of greater benefit to participants, but at 1 year no differences were apparent in uptake of strategies discussed in home versus phone visits. Conclusion Adaptations to the program to increase implementation include using a leader who is a non-health professional, and omitting the home visit. Our research demonstrated that a non-health professional leader can conduct Stepping On with adequate fidelity, however non-health professional leaders may benefit from increased training in certain aspects of Stepping On. A phone call may be substituted for the home visit, although short-term benefits are greater with the home visit.